Kajian Brand Strategy Roadmap (Studi Kasus Starbucks Coffee) - Sultan Arif Rahmadianto (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2019)
Today, business competition is no longer refers to the problem of product quality but on the issue of brand. A good brand will increase the quality of the product in the eyes of consumers by itself. The purpose of this research is to find out and analyze the brand strategy in brand